The Effects of Social Media Marketing, Lifestyle, and Brand Trust on Decisions Purchase MS Glow Products in Yogyakarta - Wunu, Lusia Arie Susanti; Fadilah, Muinah; Maharani, Bernadetta Diansepti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this study is to ascertain how social media marketing and lifestyle brand trust affect Yogyakarta consumers' decisions to buy MS Glow products. Quantitative research is the kind that is being used. Users of MS Glow in Yogyakarta make up the study's population, sample in this study is 160 people, The dissemination strategy of the questionnaire uses the Sempel retrieval approach. The results of data analysis with a significant 0,05 show that social media marketing has a positive and significant effect on the purchase decision of MS Glow products in Yogyakarta, lifestyle has a positive and significant effect on the purchase decision of MS Glow products in Yogyakarta, brand trust has a positive and significant effect on the purchase decision of MS Glow products in Yogyakarta and social media marketing, lifestyle and brand decisions simultaneously influence the purchase decision of MS Glow products in Yogyakarta.